Old forest structural development drives complexity of nest webs in a naturally disturbed boreal mixedwood forest landscape - Cadieux, Philippe; Drapeau, Pierre; Ouellet-Lapointe, Ugo; Leduc, Alain; Imbeau, Louis; Deschênes, Réjean; Nappi, Antoine (Frontiers in Forests and Global Change, 2023)
Structural complexity generated by forest development processes and tree species compositional changes provide key habitat features for vertebrate communities that rely upon tree size and decay processes for foraging, denning or nesting. Complexity of forest structure in old stands could not only be key for harboring increased taxonomic species diversity but also greater functional diversity through more complexity in networks of tree cavity dependent species. Using a nest web approach that hierarchically links cavity-bearing trees with cavity formation agents (natural decay processes and avian excavators) and cavity users (non-excavator species), we compared network characteristics of nest webs along a time since fire gradient in a naturally disturbed boreal mixedwood forest landscape in eastern North America. Since 2003, twelve 24 to 40 ha plots ranging from 61 to more than 245 years after fire were surveyed at the Lake Duparquet Research and Teaching Forest in Abitibi, Quebec, Canada to detect active nesting and denning cavities. We found that network complexity both in terms of number of vertebrate species and number of interactions among species, increased along the age gradient and was significantly higher in the older stands than predicted by chance. Whereas cavity-nesting communities in old forests used a higher diversity of tree species over a wide range of decay stages, trembling aspen remained a key cavity-bearing tree throughout the age gradient. Woodpeckers were the main cavity formation agents whereas less than 1% of cavities originated from natural decay. The structural development of older forests is thus a driver for functional diversity in cavity-using vertebrate communities through higher interaction richness in nest webs, among cavity-bearing trees, excavators and non-excavating users. The pivotal contribution of the entire gradient of old forest cover types to the overall complexity of nest webs in the boreal mixedwood zone is also a key for the resilience of the cavity-using vertebrate community to natural disturbances. We discuss how such resilience may be compromised by even-aged industrial timber harvesting with short rotations that shifts the age structure of boreal landscapes towards regenerating and young pole forests whereas old forest cover types become below their historical range of variability.